STAKHOLDERS' EFFORTS IN EMPOWERING FISHERMEN'S WIVES THROUGH DRIED FISH PRODUCTION IN NAGARI LAKITAN, SOUTH COAST REGENCY: UPAYA STAKHOLDERS DALAM PEMBERDAYAAN ISTRI NELAYAN MELALUI PRODUKSI IKAN KERING DI NAGARI LAKITAN KABUPATEN PESISIR SELATAN - Dania Azzhura; Fitri Eriyanti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research was conducted in Nagari Lakitan, which is one of the nagari located in the coastal area in the South Coast Regency, which has the potential to develop dried fish production processing to increase the economic income of the community in the area. The purpose of this study is to find out how the efforts of stakeholders related to the empowerment of fishermen's wives in Nagari Lakitan through dried fish production, as well as inhibiting factors in carrying out empowerment. This type of research is qualitative using a descriptive approach. The data collection techniques used in this study are interviews, observations and documentation. In processing data, this study uses data analysis techniques in the form of data reduction, data presentation and conclusion drawn. Then to test the validity of the data in this study, the author uses the triangulation technique of sources and methods. The results of this study show that there are 2 factors that hinder stakeholders in implementing empowerment, namely the unavailability of budget and the limited number of personnel. Furthermore, the forms of efforts made by stakeholders to empower the wives of dry processing fishermen in Nagari Lakitan, namely 1) sustainable skills development, 2) increased access to fish processing equipment assistance, and 3) training assistance to fishermen's wives.